Haplotype Map of Sickle Cell Anemia in Tunisia. (2nd July 2014) - Moumni, Imen; Ben Mustapha, Maha; Sassi, Sarra; Zorai, Amine; Ben Mansour, Ikbel; Douzi, Kais; Chouachi, Dorra; Mellouli, Fethi; Bejaoui, Mohamed; Abbes, Salem
Abstract : β -Globin haplotypes are important to establish the ethnic origin and predict the clinical development of sickle cell disease patients (SCD). To determine the chromosomal background of β S Tunisian sickle cell patients, in this first study in Tunisia, we have explored four polymorphic regions of β -globin cluster on chromosome 11. It is the 5′ region of β - LCR-HS2 site, the intervening sequence II (IVSII) region of two fetal (γ G and γ A ) genes and the 5′ region of β - globin gene. The results reveal a high molecular diversity of a microsatellite configuration describing the sequences haplotypes. The linkage disequilibrium analysis showed various haplotype combinations giving 22 "extended haplotypes". These results confirm the utility of the β -globin haplotypes for population studies and contribute to knowledge of the Tunisian gene pool, as well as establishing the role of genetic markers in physiopathology of SCD.